Forest cover modulates diversity and morphological traits of ants in highly fragmented tropical forest landscapes - Ahuatzin, Diana A. (2022)
Landscape changes in tropical environments result in long-lasting and complex changes in biodiversity that involve several biological responses (e.g., loss of species diversity and functional diversity). Both taxonomic and functional diversity might respond differently to land-use change, and this response might also vary depending on several factors, such as the taxonomic group or landscape context. Even though each level of diversity expresses different properties of the community structure, studies characterizing the species community in human-dominated landscapes have often only focused on patterns involving taxonomic diversity. Here, we evaluated different descriptors of taxonomic (i.e., richness, diversity, and dominance) and functional entropy (i.e., richness, diversity, and redundancy) and the taxonomic and functional composition of ants in a forest cover gradient (%) in 16 highly fragmented tropical humid forest landscapes in Mexico. We found that all descriptors of taxonomic diversity decreased along a gradient of forest loss. Furthermore, functional redundancy was the only component of functional diversity that was positively associated with forest cover (%). These findings suggest an ecological backup of functions provided by species in landscapes with higher forest cover, protecting these landscapes against habitat disturbance or species loss. We also observed that landscapes with larger forest cover were inhabited by ant species with larger interocular distances and smaller femurs, which could allow predator ants the exploitation of ground cracks and higher mobility in leaf-litter microhabitats. Our results highlight the importance of the primary forest as a reservoir of the taxonomic and functional diversity of ants in highly fragmented tropical rainforest landscapes.